Nutrition Management Practises in Critical Care in Tertiary Hospitals - A Survey from India - Edwin Pathrose, Sanjith Saseedharan (International Journal of Innovative Research in Medical Science, 2017)
Introduction: To observe nutrition practises followed by intensive care units (ICUs) of tertiary care hospitals of various sizes. Method: A paper-based survey was performed in 20 tertiary care ICUs across Mumbai, India. ICUs with as few as 9 beds and as many as 100 beds participated in the survey. ICUs were classified as small, medium and large based on the number of beds. Results: No ICU had occupancy of less than 63% at the time of the survey. Most ICUs, regardless of size, reported clear fluid as the preferred first feed and bolus as the preferred EN. Most large hospital ICUs prescribed up to 100% formula feeds as opposed to most small and medium ICUs. Only two large ICUs reported that they administer dietician prescribed formula feeds, whereas most ICUs administered physician prescribed formula feeds. Conclusion: The choice of bolus as EN indicates a preference for kitchen feeds. This may be attributed to cost of formula feeds. Most ICUs reported that ICU physicians recommended formula feeds.